Ghanaians Might Be at Risk of Inadequate Dietary Intake of Potassium. (6th December 2016) - Yawson, David Oscar; Adu, Michael Osei; Ason, Benjamin; Armah, Frederick Ato; Boateng, Emmanuel; Quansah, Reggie
Abstract : Adequate dietary intake of potassium (K) helps fight noncommunicable diseases (NCDs), mainly hypertension and cardiovascular diseases. This paper (i) estimated the K intake of Ghanaian population using food supply and food composition data and (ii) compared this estimate with the WHO recommended requirement for K in order to assess if there is a risk of inadequate K intake. Food supply data (1961–2011) was obtained from the FAO Food Balance Sheet (FBS) to derive trends in food and K supply. The average food supply in the FBS for 2010 and 2011 was used in assessing the risk of inadequate dietary intake of K. The K contents of the food items were obtained from food composition databases. The mean K supply per capita per day was approximately 856 mg. The assessment suggests a potentially large risk of inadequate dietary K supply at both individual and population levels. The results suggest the need for assessing options for managing K deficiency, including assessment of K supplying power of soils and K fertilizer management in food crop production systems, as well as empirical estimates of K content of food items (including those underreported in the FBS) and mixed diets in Ghana.